Inverted papilloma of the hard palate masquerading as a carcinoma - A A Kallianpur; S Goyal; R Yadav; D K Muduly (Wolters Kluwer Medknow Publications, 2014)
Inverted papilloma (IP) is a rare, benign tumor of the nose and paranasal sinus. However, it is locally aggressive, the recurrence rate is high and malignant transformation is possible. Until now, IP of the hard palate has rarely been reported in the literature. Here, we reported a case with IP of the hard palate, which clinically presented as a carcinomatous growth. The management of IP is complete surgical excision with a close follow-up to detect early recurrence and/or malignant transformation.